Phospholemman Phosphorylation Regulates Vascular Tone, Blood Pressure, and Hypertension in Mice and Humans. Issue 11 (18th December 2020) - Boguslavskyi, Andrii; Tokar, Sergiy; Prysyazhna, Oleksandra; Rudyk, Olena; Sanchez-Tatay, David; Lemmey, Hamish A.L.; Dora, Kim A.; Garland, Christopher J.; Warren, Helen R.; Doney, Alexander; Palmer, Colin N.A.; Caulfield, Mark J.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Although it has long been recognized that smooth muscle Na/K ATPase modulates vascular tone and blood pressure (BP), the role of its accessory protein phospholemman has not been characterized. The aim of this study was to test the hypothesis that phospholemman phosphorylation regulates vascular tone in vitro and that this mechanism plays an important role in modulation of vascular function and BP in experimental models in vivo and in humans. Methods: In mouse studies, phospholemman knock-in mice (PLM 3SA ; phospholemman [FXYD1] in which the 3 phosphorylation sites on serines 63, 68, and 69 are mutated to alanines), in which phospholemman is rendered unphosphorylatable, were used to assess the role of phospholemman phosphorylation in vitro in aortic and mesenteric vessels using wire myography and membrane potential measurements. In vivo BP and regional blood flow were assessed using Doppler flow and telemetry in young (14–16 weeks) and old (57–60 weeks) wild-type and transgenic mice. In human studies, we searched human genomic databases for mutations in phospholemman in the region of the phosphorylation sites and performed analyses within 2 human data cohorts (UK Biobank and GoDARTS [Genetics of Diabetes Audit and Research in Tayside]) to assess the impact of an identified single nucleotide polymorphism on BP. This single nucleotide polymorphism was expressed in human embryonic kidney cells, and its effect on phospholemman phosphorylation was determined using Western blotting. Results: Phospholemman phosphorylation at Ser63 and Ser68 limited vascular constriction in response to phenylephrine. This effect was blocked by ouabain. Prevention of phospholemman phosphorylation in the PLM 3SA mouse profoundly enhanced vascular responses to phenylephrine both in vitro and in vivo. In aging wild-type mice, phospholemman was hypophosphorylated, and this correlated with the development of aging-induced essential hypertension. In humans, we identified a nonsynonymous coding variant, single nucleotide polymorphism rs61753924, which causes the substitution R70C in phospholemman. In human embryonic kidney cells, the R70C mutation prevented phospholemman phosphorylation at Ser68. This variant's rare allele is significantly associated with increased BP in middle-aged men. Conclusions: These studies demonstrate the importance of phospholemman phosphorylation in the regulation of vascular tone and BP and suggest a novel mechanism, and therapeutic target, for aging-induced essential hypertension in humans.